Teaching and practicing nursing code of ethics and values in the Gambia - Haddy Tunkara Bah; Jainaba Sey-Sawo (Elsevier, 2018)
Nursing has a professional autonomy which goes along with responsibility and accountability of nursing actions. Nursing practice should always be guided by a code of ethics and values. However, the concepts of nursing ethics and values are contained only in the introductory courses of the nursing curriculum in the Gambia. Many nurse educators and clinicians are not knowledgeable about the code of ethics of nursing in this country. Lectures on nursing ethics and values are mostly taught by invited guest lecturers in only one or two lecture sessions of the entire nurse training programme. Teaching nursing ethics and values at clinical level is poor due to the limited number of trained senior nurses to serve as mentors and supervisors for students and junior nurses. Most of the Gambian public health facilities do not have standard guidelines on various nursing procedures. Low status of nurses and conformist style of training nurses hinder the effective implementation of the code of nursing ethics and values among professional nurses in this country. There is, therefore, inadequate teaching and implementation of the code of nursing ethics and values which calls for urgent reforms in nursing education and practice to improve the standard and image of the Nursing Profession in the Gambia. Keywords: Teaching, Implementing, Nursing, Ethics, Values, The Gambia